2014
DOI: 10.1159/000368803
|View full text |Cite
|
Sign up to set email alerts
|

Ezetimibe-Mediated Protection of Vascular Smooth Muscle Cells from Cholesterol Accumulation through the Regulation of Lipid Metabolism-Related Gene Expression

Abstract: Background: Ezetimibe is a potent inhibitor of Niemann-Pick type C1-Like 1 and has been approved for the treatment of hypercholesterolemia. Our preliminary study showed that ezetimibe promotes cholesterol efflux from vascular smooth muscle cells (VSMCs). Our aim was to investigate the cellular mechanisms underlying the ezetimibe actions. Methods and Results: Rat VSMCs were converted to foam cells by incubation with cholesterol:methyl-F-cyclodextrin. The intracellular free cholesterol, total cholesterol, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It was reported that sterol regulatory element binding proteins (SREBPs) expression was mainly regulated by cellular cholesterol and CAV1 was negatively regulated by SREBPs ( Xu et al, 2010 ; Fernandez-Rojo and Ramm, 2016 ). Besides, several studies have suggested that there is a molecular loop of reciprocal control between liver CAV1 and lipid metabolism ( Gong et al, 2014 ; Fernandez-Rojo and Ramm, 2016 ). Therefore, the decreased CAV1 level after inhibiting AMPK activation may be the consequence of abnormal lipid metabolism and increased SREBPs protein expression in cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that sterol regulatory element binding proteins (SREBPs) expression was mainly regulated by cellular cholesterol and CAV1 was negatively regulated by SREBPs ( Xu et al, 2010 ; Fernandez-Rojo and Ramm, 2016 ). Besides, several studies have suggested that there is a molecular loop of reciprocal control between liver CAV1 and lipid metabolism ( Gong et al, 2014 ; Fernandez-Rojo and Ramm, 2016 ). Therefore, the decreased CAV1 level after inhibiting AMPK activation may be the consequence of abnormal lipid metabolism and increased SREBPs protein expression in cells.…”
Section: Discussionmentioning
confidence: 99%
“…CAV-1 may mediate cellular cholesterol efflux to high-density lipoprotein (HDL) [ 4 , 5 ]. Several studies have revealed that CAV-1 protein overexpression markedly reduced total cholesterol and free cholesterol (FC) content as well as their accumulation in lipid-loading cells [ 6 8 ]. In CAV-1-deficient mice, moderately elevated whole-lung cholesterol content, impaired liver regeneration, cardiovascular disorders, and FC accumulation in mitochondrial membranes resulted in mitochondrial diseases [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%